Impact of COVID-19 Pandemic on Gender Mainstreaming Implementation in 2020 in Batu City, East Java - Mely Noviryani; Sri Minarti; Keppi Sukesi (Sawwa: Jurnal Studi Gender, 2021)
The COVID-19 pandemic during 2020 has impacted health aspects, social life, economics, and politics. Large-scale social restriction policies and health protocols have been applied in almost all regions in East Java. This study aims to identify the impact of the COVID-19 pandemic on gender mainstreaming implementation in Batu City and how the local government responds to it. Focus Group discussion (FDG) with the local government was run to obtain data. By using seven elements commonly used to evaluate gender mainstreaming implementation, this study shows that the COVID-19 pandemic has remarkably impacted gender mainstreaming implementation. No specific policies have yet been made within the gender mainstreaming framework. PUG institutions are also not involved in the COVID-19 task force. There have been efforts to respond to the impact in some sectors but not all in gender mainstreaming. Human resources have not been explicitly prepared in dealing with women’s problems during the COVID-19 pandemic. The budget is reallocated so that even routine activities cannot be fully carried out. Community participation is also helpful in tackling the pandemic, although it has not specifically responded to the impacts. This study implies the importance of integrating a disaster perspective in monitoring and evaluating gender mainstreaming.